2019
DOI: 10.15171/jlms.2019.36
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Orthodontic Expansion Assisted by Unilateral Alveolar Corticotomy and Low-Level Laser Therapy: A Novel Approach for Correction of a Posterior Unilateral Cross-Bite in Adults

Abstract: Introduction: The treatment of a true unilateral posterior crossbite often requires asymmetric maxillary expansion; however, this is challenging to achieve with conventional expansion methods because of several biomechanical limitations. In this paper, we introduce a new protocol for the treatment of a unilateral posterior crossbite in adults based on maxillary orthodontic expansion assisted by corticotomy and low-level laser therapy (LLLT) performed on the crossbite side. Methods: The study sample included 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
0
15
0
5
Order By: Relevance
“…The use of skeletal anchorage is getting widespread among orthodontists since it facilitates the management of complex orthodontic biomechanics; as a consequence, skeletal anchorage can be useful in treating borderline cases such as transversal maxillary deficiency in adults. In this respect, miniscrews-assisted rapid maxillary expansion was found to effectively open the mid-palatal suture in adults without the necessity to undergo orthognathic surgery [12,24,[28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The use of skeletal anchorage is getting widespread among orthodontists since it facilitates the management of complex orthodontic biomechanics; as a consequence, skeletal anchorage can be useful in treating borderline cases such as transversal maxillary deficiency in adults. In this respect, miniscrews-assisted rapid maxillary expansion was found to effectively open the mid-palatal suture in adults without the necessity to undergo orthognathic surgery [12,24,[28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] The red and near-infrared regions of the spectrum represent the most effective ranges of irradiation, since they thoroughly penetrate into the living tissues to induce cell proliferation and differentiation without overheating the tissues. 8,12,22,23 In vitro and in vivo studies also suggested that irradiation dose could influence the rate of orthodontic movement. In particular, the effective dosage that was proven to accelerate canine retraction during space closure…”
Section: Discussionmentioning
confidence: 99%
“…20 However, we decided to enroll 100 subjects (50 for each group) counteracting any potential incompleteness of data. The enrollment process was based on the following criteria: (1) age between 13 and 30 years, (2) permanent mandibular dentition, (3) angle class I malocclusion, (4) lower 6-6 mild crowding measured on dental cast, (5) no diastema or spaces in the lower arch, (6) no ectopic teeth, (7) no extractions required or intraoral or extraoral auxiliary devices, and (8) no previous orthodontic treatment.…”
Section: Human Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…PBM can create a favorable environment for tooth movement, as two types of host responses occur in the irradiated tissues. First, photobiomodulation increases the production of mitochondrial ATP by upregulating the cytochrome c oxidase [12,14,[39][40][41][42][43][44][45] and promotes the cellular viability and the expression of osteocalcin in the tension areas of PDL [12][13][14][15][39][40][41][42][43]. This increased metabolic activity accelerates cellular turnover (osteoclast, osteoblast, and fibroblasts) [44][45][46][47][48][49][50][51][52][53] and the production of cytokines involved in the bone remodeling, mainly the IL-1b [46,[54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%